IMMERSIVE VIRTUAL REALITY FOR EXPERIENTIAL LEARNING - Cau, Marco (My University, 2021)
Immersive virtual reality is any computer-generated environment capable of fooling the user’s senses with a feeling of presence (being there). Two different types of hardware are usually used to access immersive virtual reality: Head Mounted Displays (HMD) or Cave Automated Virtual Environment (CAVE). Due to its ability to generate any kind of environment, either real or imaginary, immersive virtual reality can be used as a tool to deliver experiential learning, as described by Kolb (1984) in his experiential learning circle model. Such model identifies four different steps that, as part of a circle, describe the process of learning by experiencing something, these steps are: (1) concrete experience, (2) observations and reflections, (3) formulation of abstract concepts and generalization, (4) testing implications of concepts in new situations. Immersive virtual reality has been out for decades, but in spite of the big buzz around it, a large adoption of the technology has not occurred yet. One of the main barriers to adoptions is the high cost of gear needed. However, recent development in technology are pushing prices down. For instance, Google Cardboard offers a very inexpensive way to experience virtual reality through smartphones. Moreover, the price of HMD and the powerful computers needed to run virtual reality software are expected to fall as it already happened with desktop computers before. The Technology Acceptance Model (TAM), as introduced by Davis (1989), is an attempt to understand the factors behind the adoption of new technologies. In particular, this model introduces the two key concepts of (1) perceived usefulness and (2) perceived ease of use. Looking at these, the manuscript attempts to bring some light in the current state of the adoption. The findings of this study have both theoretical and managerial implications, useful both to schools and vendors. The main finding of this study is that more research is needed to understand how people learn in immersive virtual reality, and how to develop software capable of delivering experiential learning. A tighter collaboration between schools, students, manufacturers, software developers seems to be the most viable way to go.